Penguatan Pengelolaan Ternak Wakaf Hibah Produktif melalui Fermentasi Pakan Ternak sebagai Alternatif Pemberdayaan Santri menuju Pesantren Yatim yang Mandiri - Nihayatu Aslamatis Solekah; Ulfi Kartika Oktaviana (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2017)
Strengthening of productive wakaf livestock management on Himmatun ayat foundation in the form of goat farming which originally amounted to 31 tail to 80 tails and 2 cattle, given the geographical condition of the cracked city that the land is limestone, the main problem is the availability of feed. Because the managers are orphaned students themselves then the initial get goat grant, a lot of goats are dead. The problem is quite serious is during the rainy season lack of supply of animal feed. In the dry season orphaned santri living herding goats in rain-fed rice fields that are not cultivated because it is a rain-fed rice field. Goat and cattle feed in the rainy season is a fermentation of mixed kale leaves, bran and yeast. So there is a symbiosis of mutualism in which the survival of orphaned santri is dependent on the productive grant of goats as well as vice versa. Some potentials that can be empowered to benefit from the social, economic and environmental aspects (1) It is necessary to analyze the feasibility level of goat farm management, especially the fulfillment of animal feed for productive grants, so that the farm will continue to grow so that the boarding school can be independent from the aspect of fulfilling the needs of the orphans living in the pesantren. (2) The need for fermented animal wakaf fermentation training for orphan students so as to create the fulfillment of animal wakaf feed throughout the year. (3) The need for assistance in the management of endowment grants productive goat farming, especially aspects of marketing and human resources aspects so that it will form the spirit of entrepreneurship orphan students to independently manage wakaf productive grant goat and cattle farms.